2006
DOI: 10.1093/aob/mcl037
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Increase of Mean Daily Temperature Adversely Affects Fruit Set of Lycopersicon esculentum by Disrupting Specific Physiological Processes in Male Reproductive Development

Abstract: The research indicated that failure of tomato fruit set under a moderately increased temperature above optimal is due to the disruption of sugar metabolism and proline translocation during the narrow window of male reproductive development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
262
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(282 citation statements)
references
References 31 publications
19
262
0
1
Order By: Relevance
“…The highest fruit TSS was obtained from shading by maize plants followed by Robin algae and Purshade treatments, the lowest TSS was obtained by shading by green net treatment. The obtained results agreed with those of Kinet and Peet (1997), Safia et al (2002), Foolad (2005) and Sato et al (2006). Values having an alphabetical letter in common within column do not statistically differ, using Duncan's multiple range test at 5 %.…”
Section: Chemical Characters Of Tomato Fruitssupporting
confidence: 89%
See 1 more Smart Citation
“…The highest fruit TSS was obtained from shading by maize plants followed by Robin algae and Purshade treatments, the lowest TSS was obtained by shading by green net treatment. The obtained results agreed with those of Kinet and Peet (1997), Safia et al (2002), Foolad (2005) and Sato et al (2006). Values having an alphabetical letter in common within column do not statistically differ, using Duncan's multiple range test at 5 %.…”
Section: Chemical Characters Of Tomato Fruitssupporting
confidence: 89%
“…On the contrary, the lowest previous parameters were obtained with those plants grown without protection (control) because of the exposing to high temperature .However, poor fruit set at high temperature has also been associated with low levels of carbohydrates and growth regulators released in plants tissues (Safia et al, 2002). Also under high temperatures, fruit set in tomato plants failed due to the disruption of sugar metabolism (Sato et al, 2006 andMedany et al, 2009). The increasing in tomato total yield under green net maybe due to the plants don't suffer from the heat stress under the net, the plants has good vegetative growth, better pollination and finally higher yield (Safia et al, 2002).…”
Section: Number Of Clusters Fruit Set (%) Early Total Yield (Ton/ mentioning
confidence: 99%
“…In anthers of tolerant cultivars, higher constitutive expression of heat shock proteins and heat shock transcription factors was observed (Bita et al, 2011). Moreover, higher invertase activity was reported upon heat stress in tolerant cultivars (Dorion et al, 1996;Li et al, 2012), and downregulation of a proline transporter was observed in sensitive cultivars (Sato et al, 2006). This information may be helpful for understanding tolerance mechanisms, but to be useful for breeding of temperature-tolerant crops, allelic variation in genes promoting heat tolerance needs to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Besides maize, many other cereals, such as wheat (Triticum aestivum), barley (Hordeum vulgare), and rice (Oryza sativa), are affected by high temperatures during the reproductive phase (Barnabás et al, 2008). Negative effects of heat stress have also been reported for other important crops from various plant families, such as tomato (Solanum lycopersicum) (Sato et al, 2002(Sato et al, , 2006 and pepper (Capsicum annuum) (Marcelis et al, 2004) from the Solanaceae family, canola and mustard (Brassica juncea, Brassica rapa, and Brassica napus) (Angadi et al, 2000;Gan et al, 2004) from the Brassicaceae family, soybean (Glycine max) (Djanaguiraman et al, 2013) and chickpea (Cicer arietinum) (Clarke and Siddique, 2004) from the Fabiaceae family, and peach (Prunus persica) (Hedhly et al, 2005) and cherry (Prunus avium) (Hedhly et al, 2004) from the Rosaceae family. Thus, heat stress is an important factor that affects crop yields worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation